EFL Preservice Teachers’ Experiences Of Teaching English Using Differentiated Instruction In Kurikulum Merdeka - Elsa; Nur Hasanah Safei; Dewi Atikah; Rezki, Anita (IAIN KENDARI, 2026)
This case study aims to explore the experiences of EFL preservice teachers in teaching English using the differentiated instruction process in the context of the Kurikulum Merdeka. The participants were 10 EFL students who had completed a teaching internship activity. Online reflection and semi-structured interviews were used to obtain qualitative data for this study. The results of the data analysis showed that there are four things that are the most important part of the differentiated instruction process, the first is designing teaching materials from differentiated instruction; using textbooks, digital media, worksheets and optional assignments, communication and collaboration tools, and initial and ongoing assessments. The second is the implementation of differentiated instruction; grouping students, varying learning materials, and providing feedback. The third is the adaptation; differentiating the level of difficulty of tasks, freeing students to choose the form of tasks, and making games. Fourth is how the experience is felt by EFL preservice teachers; experienced challenges, teacher competency development, and effectiveness. This study can specifically show that the use of the differentiated instruction process plays a role in supporting increased student engagement, learning motivation, and deeper understanding of the material in English learning in schools that implement the Kurikulum Merdeka. Keywords:‎ case study; EFL preservice teachers’ experiences; Kurikulum Merdeka; process of differentiated instruction.